Evaluation of the sequence method as a tool to assess spontaneous baroreflex in reptiles - Filogonio, Renato; Orsolini, Karina F.; Castro, Samanta A.; Oda, Gustavo M.; Rocha, Gabriella C.; Tavares, Driele; Abe, Augusto S. [UNESP]; Leite, Cléo A. C. (Wiley, 2019)
The sequence method is an alternative to the traditional pharmacological approach (i.e., the Oxford technique) used to calculate baroreflex gain (G) in mammals. Although the sequence method assesses baroreflex by measuring spontaneous events of blood pressure regulation, the pharmacological method relies on the injection of vasoactive drugs that impact the baroreflex mechanism itself. The sequence method might be relevant for dynamic measurement of baroreflex modulation but it was never validated for vertebrates with low heart rate. Hence, we tested the sequence method in three species of reptiles and compared the results with those provided by the classic pharmacological method. G was similar between both methods and values correlated when parameters for the sequence method were set at delay 0 or 1 (i.e., the baroreflex system responds immediately to blood pressure changes or after 1 heartbeat). Calculation of the baroreflex effectiveness index was adequate at a minimum of 300 cycles and a delay of 1 for the three species. Therefore, the sequence method has been validated to investigate baroreflex regulation in reptiles, enabling studies during dynamic alterations in homeostasis.
Keywords: 3R principle; baroreflex effectiveness index; baroreflex saturation; baroreflex threshold; baroreflex-operating range; Oxford technique; pharmacological method